ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI PROVINSI NUSA TENGGARA BARAT, INDONESIA - Supriaman Supriaman (Program Studi Ekonomi Syariah IAI Muhammadiyah Bima, 2020)
Poverty is a fundamental and multidimensional problem in economic development, especially in developing countries such as Indonesia and underdeveloped region such as Nusa Tenggara Barat province. The percentage of poor people in Nusa Tenggara Barat is relatively higher compared to the percentage of poor people in national level. This study aims to analyze the factors which influence the poverty level in Nusa Tenggara Barat. By employing a panel data regression of 10 Regencies/Cities along 2010-2015, the study finds that the work force skill, investment and income per capita have significant effect to poverty level. The coefficient of work force skill has the highest impact to the level of poverty, which means that that variable is a major factor in reducing poverty in 10 Regencies/Cities of West Nusa Tenggara Province. Based on the results, the study recommends the policy that promote poverty alleviation need to be strengthened by communities and governments.